The problem of personal development in the conditions of renewal of informational culture of society - Галета, Ярослав Володимирович (ScienceRise: Pedagogical Education, 2016)
The problem of personal formation in the modern conditions of growth of the role of informational-communicational technologies becomes the one of topical problems in the field of pedagogical studies. The volume of information, informational resources and correspondent technologies significantly influence both the different sides of social life and the processes of human personal formation in particular. This article is devoted to the analysis of approaches, ideas, concerning the study of the features of personal formation in informational society. The research demonstrated that scientists connect the solution of this problem with formation of the human informational culture. In the work was presented the process of perception of the essence of this category and also outlined the series of notions, which essence allows specify the content of notion “informational culture”. These categories are: information, culture, informational needs. The special attention in the article was paid to the development of informational needs in educational institutions. In particular there were denoted the directions and means for solving this problem